2008
DOI: 10.1111/j.0908-8857.2008.04390.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for improved immune response of extra‐pair nestlings in collared flycatcher Ficedula albicollis

Abstract: Extra‐pair paternity is common in many socially monogamous bird species. Increasing evidence suggests that extra‐pair copulations are female‐driven, but benefits for females mating outside social pair‐bonds are still poorly understood. The most influential explanation, “good genes” hypothesis, states that females mated socially with low quality males, engage in extra‐pair copulations to obtain genetic benefits for their progeny. According to this model, enhanced performance of extra‐pair offspring is expected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 53 publications
0
7
2
Order By: Relevance
“…For example, EPY occurred in early eggs from two independent samples obtained in our population in different years (Krist et al. 2005 and this study), while no such effect was found in Polish (Wilk et al. 2008) and Hungarian (Rosivall et al.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…For example, EPY occurred in early eggs from two independent samples obtained in our population in different years (Krist et al. 2005 and this study), while no such effect was found in Polish (Wilk et al. 2008) and Hungarian (Rosivall et al.…”
Section: Discussioncontrasting
confidence: 43%
“…However, the distribution of EPY in laying order may differ both between and within species. For example, EPY occurred in early eggs from two independent samples obtained in our population in different years (Krist et al 2005 and this study), while no such effect was found in Polish (Wilk et al 2008) and Hungarian (Rosivall et al 2009) populations of the species. If EPY occurred in late eggs (Riley et al 1995), this could lead to an underestimation of paternal genetic effects owing to the counteractive effect of hatching asynchrony.…”
Section: Extra-pair Young and Maternal Effectscontrasting
confidence: 41%
“…Despite inconclusive empirical support within and across species (e.g. Kleven et al, 2006;Wilk et al, 2008;Bollmer et al, 2012), indirect benefits for EPP remain the dominant hypothesis for this behaviour, although alternatives have been advanced that suggest EPP is costly to females, is not explicitly adaptive to females or is not strictly femaledriven (Westneat & Stewart, 2003;Arnqvist & Kirkpatrick, 2005;Forstmeier et al, 2011Forstmeier et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Krist et al (2005) found that EP offspring occur significantly more often in earlier‐laid eggs in collared flycatchers Ficedula albicollis . Four other studies have reported either more EP offspring in earlier‐laid eggs (Cordero et al 1999), more EP offspring in later‐laid eggs (Riley et al 1995), or no association between offspring paternity and laying/hatching position (Barber and Robertson 2007, Wilk et al 2008). However, sample sizes in several of these latter studies were small and so results may best be considered preliminary.…”
mentioning
confidence: 98%